(untitled) (Research, Society and Development, 2022)
In the present study, the objective was to evaluate the adoption of good agricultural practices, productivity and commercialization, in family coffee farming ventures, led by men and women, youth and adults, in coffee growing regions of Minas Gerais. As a methodology, to recognize the situation, a structured questionnaire was applied to 309 family farmers participating in the sustainability program of Fundação Hanns R. Neumann Stiftung do Brasil. The frequency data, chi-square distribution test and hypothesis, for the comparison of productivity averages and coffee commercialization price by classified groups, according to age and gender, were analyzed in the statistical software R. The results indicated differences, in terms of adoption of some good agricultural practices, in enterprises led by the groups studied. Coffee productivity was the same in all properties, regardless of the observed group, however, the best access to commercialization prices was obtained by women. It was concluded that the leadership of men and adults prevails over the leadership of women and young people, but there is a potential for the adoption of sustainable innovations, especially in enterprises led by women and young people.